Saffron Aqueous Extract Prevents Metabolic Syndrome in Patients with Schizophrenia on Olanzapine Treatment: A Randomized Triple Blind Placebo Controlled Study - Fadai, F.; Mousavi, B.; Ashtari, Z.; Ali beigi, N.; Farhang, S.; Hashempour, S.; Shahhamzei, N.; Zahra Bathaie, S. (Pharmacopsychiatry, 2014)
Objective: The aim of this study was to assess whether saffron aqueous extract (SAE) or its active constituent, crocin, prevents olanzapine-induced metabolic syndrome (MetS) and insulin resistance in patients with schizophrenia.Methods: 66 patients diagnosed with schizophrenia who were on olanzapine treatment (5–20 mg daily) were randomly allocated to receive a capsule of SAE (n=22; 30 mg daily), crocin (n=22; 30 mg daily) or placebo (n=22) in a 12-week triple-blind trial. Patients were screened not to have MetS at baseline and further assessment was done at weeks 6 and 12. Measurement of fasting blood glucose (FBS) and serum lipids were repeated at weeks 2, 6 and 12. Fasting blood levels of insulin and HbA1c were also measured at baseline and week 12. HOMA-IR and HOMA-β were determined to evaluate insulin resistance.Results: 61 patients completed the trial and no serious adverse effects were reported. Time-treatment interaction showed a significant difference in FBS in both SAE and crocin groups compared to placebo (p=0.004). In addition, SAE could effectively prevent reaching the criteria of metabolic syndrome (0 patients) compared to crocin (9.1%) and placebo (27.3%) as early as week 6.Conclusion: SAE could prevent metabolic syndrome compared to crocin and placebo. Furthermore, both SAE and crocin prevented increases in blood glucose during the study.
Keywords: saffron; olanzapine; FBS; metabolic syndrome; insulin resistance